PI3K/Akt pathway and neuroinflammation in sepsis-associated encephalopathy - Guo Yang; Yu Yonghao (Open Medicine)
Sepsis-associated encephalopathy (SAE) is a complex neurological complication of sepsis involving activation of microglia in the central nervous system (CNS), blood–brain barrier (BBB) dysfunction, neurotransmitter dysfunction, impaired brain metabolism, and mitochondrial dysfunction. Neuroinflammation is a critical component of the pathogenesis. The phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) signaling pathway, as a key intracellular signaling pathway, plays a crucial role in regulating neuroinflammation, maintaining the integrity of the BBB, and promoting neuronal cell survival.